Comparison between the Concentrations of Ammonium Ion and the Results of the Microbiological Examination of Some Drinking Water Samples - الخير معروف; عشيش نور (Latakia University Journal -Medical Sciences Series, 2021)
Water pollution is one of the biggest environmental problems facing humans at this age as a result of the widespread use of water in the disposal of various human and industrial wastes, which exacerbated the problem of pollution of fresh water in rivers, lakes and groundwater, which made water less suitable for drinking due to changing its physical, chemical and biological properties. This research aims to determine the ammonium ion concentrations in some drinking water sources from the groundwater in the countryside of Hama governorate by applying a color spectrophotometric method using Nessler’s reagent and comparing it with the total bacterial count and the presence of fecal coliform and Escherichia coli bacteria in the water. The samples were taken during the winter and summer seasons. It was observed that all the measured concentrations of ammonium ions and the total bacterial count were within the permissible limits corresponding to the Syrian standard specification for drinking water, except for the wells located near the stream of the Assi River, the concentrations of ammonium and the total bacterial count were higher than the permissible limits in the Asharna area wells, with complete absence for the presence of fecal coliform and Escherichia coli in all wells. Also, the ammonium concentrations and the total bacterial counts were higher in the summer and the high ammonium concentrations correspond with an increase in the total bacterial count but without the presence of pathogenic bacteria, which indicates that ammonium is an indicator of increased bacterial growth, but it is not enough to determine ammonium concentrations only to judge the suitability of drinking water.